2018
DOI: 10.1002/ange.201810297
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength‐Controlled Dynamic Metathesis: A Light‐Driven Exchange Reaction between Disulfide and Diselenide Bonds

Abstract: Wavelength‐controlled dynamic processes are mostly based on light‐triggered isomerization or the cleavage/formation of molecular connections. Control over dynamic metathesis reactions by different light wavelengths, which would be useful in controllable dynamic chemistry, has rarely been studied. Taking advantage of the different bond energies of disulfide and diselenide bonds, we have developed a wavelength‐driven exchange reaction between disulfides and diselenides, which underwent metathesis under UV light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 67 publications
1
15
0
Order By: Relevance
“…Among the wide scope of methods, metathesis reactions have become important tools enabling formation of e. g. two molecules from the other two . UV irradiation induced disulfide metathesis is based on homolytic cleavage of the disulfide bond and the subsequent cross‐reaction between resulting radicals, however, the visible light turned out to be sufficient for a diselenide exchange because of relatively low energy of Se−Se bond . The metathesis reaction in diselenide based systems is useful in designing self‐healing polymers as well as in selective surface modification e. g. for bioconjugation purposes .…”
Section: Figurementioning
confidence: 99%
“…Among the wide scope of methods, metathesis reactions have become important tools enabling formation of e. g. two molecules from the other two . UV irradiation induced disulfide metathesis is based on homolytic cleavage of the disulfide bond and the subsequent cross‐reaction between resulting radicals, however, the visible light turned out to be sufficient for a diselenide exchange because of relatively low energy of Se−Se bond . The metathesis reaction in diselenide based systems is useful in designing self‐healing polymers as well as in selective surface modification e. g. for bioconjugation purposes .…”
Section: Figurementioning
confidence: 99%
“…In contrast to the signals from PMA-Br, there were four additionally equally spaced peaks from the sonicated (PMASe) 2 sample, which could be ascribed to the generation of selenium free radicals (Figure 3a). 34 Collectively, these data proved that the chemoselectivity of bond scission was effectively improved by introducing a Se−Se group in the polymer main chain. As such, under sonication, the central Se− Se bonds can be activated predominantly over that of the unspecified C−C breakage.…”
Section: T H Imentioning
confidence: 81%
“…Our results proved the dynamic covalent diselenide bond to be an ideal mechanophore and showed that sonication offered an alternative and effective approach to generate chromic, Se-containing derivative polymers. Considering the values of the diselenide bond in adaptive and biomedical materials, ,, these findings enriched our understanding of the stimuli-responsive properties of the diselenide bond, which may help expand their applications in electronics, catalysis, therapeutics, and so on.…”
mentioning
confidence: 89%
“…Despite the advantage of the dynamics of disulfide bonds in response to biochemical cues, a practical limitation of the use of disulfide crosslinked hydrogels for cell culture is the slow thiol‐ disulfide exchange in air. [ 39‐40 ] The long gelation time often causes cell sedimentation during cell encapsulation and limits cell attachment and spreading. Alternatively, strong oxidants can be added to increase the reaction efficiency; but these agents are usually highly cytotoxic.…”
Section: Introductionmentioning
confidence: 99%